2017
DOI: 10.1038/s41598-017-09254-6
|View full text |Cite|
|
Sign up to set email alerts
|

Searching for signatures across microbial communities: Metagenomic analysis of soil samples from mangrove and other ecosystems

Abstract: In this study, we categorize the microbial community in mangrove sediment samples from four different locations within a vast mangrove system in Kerala, India. We compared this data to other samples taken from the other known mangrove data, a tropical rainforest, and ocean sediment. An examination of the microbial communities from a large mangrove forest that stretches across southwestern India showed strong similarities across the higher taxonomic levels. When ocean sediment and a single isolate from a tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 67 publications
2
36
1
1
Order By: Relevance
“…Our results showed that bacterial species had the highest relative abundance in both habitats (98%) compared to Archaea (0.22%) and Eukaryota (1.77%), whereas the most abundant bacterial Phyla are Proteobacteria, Actinobacteria, Bacteroidetes, Acidobacteria and Firmicutes, accounting for approximately 85% of the sequences in rhizosphere soil samples. These Phyla have been described as widespread and often abundant in other different soil samples (Aislabie et al, 2013;Imchen et al, 2017;Lauber et al, 2009;Yang, 2015), including Antarctic soils (Bottos et al, 2014;da Silva et al, 2017;Teixeira et al, 2013) and may constitute a core root microbiome playing a pivotal role in plant growth promotion, nutrient acquisition and abiotic stress tolerance (Chen et al, 2017). Proteobacteria is a metabolically diverse group that has been related to nutrient cycling, including carbon, nitrogen and sulfur, by degrading soluble organic molecules such as organic acids, aminoacids and sugars (Eilers et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that bacterial species had the highest relative abundance in both habitats (98%) compared to Archaea (0.22%) and Eukaryota (1.77%), whereas the most abundant bacterial Phyla are Proteobacteria, Actinobacteria, Bacteroidetes, Acidobacteria and Firmicutes, accounting for approximately 85% of the sequences in rhizosphere soil samples. These Phyla have been described as widespread and often abundant in other different soil samples (Aislabie et al, 2013;Imchen et al, 2017;Lauber et al, 2009;Yang, 2015), including Antarctic soils (Bottos et al, 2014;da Silva et al, 2017;Teixeira et al, 2013) and may constitute a core root microbiome playing a pivotal role in plant growth promotion, nutrient acquisition and abiotic stress tolerance (Chen et al, 2017). Proteobacteria is a metabolically diverse group that has been related to nutrient cycling, including carbon, nitrogen and sulfur, by degrading soluble organic molecules such as organic acids, aminoacids and sugars (Eilers et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Parameters applied were maximum E-value of 1 × 10 −5 , a minimum percentage identity of 60%, and a minimum alignment length of 15. For functional analysis comparisons, subsystems were implied to assign functional roles to genes [22,23].…”
Section: Taxonomic and Functional Annotationmentioning
confidence: 99%
“…Mangrove sediment samples were collected from eight different locations along the coastal region of Kerala according to our previous study on the Kerala mangrove resistome (Table 1) [10,11]. These mangrove ecosystems have indirect mild exposure to sewage from anthropogenic activities.…”
Section: Sampling Enrichment and Isolation Of Antibiotic-resistant mentioning
confidence: 99%
“…Table 1. Sampling locations spanning the north and central Kerala (India) were surveyed according to our previous studies [10,11] and mangrove sediments were collected in triplicate from the upper 5-10 cm in sterile sampling bags. The sampling locations and their codes are provided in first and second column, respectively.…”
Section: Sampling Enrichment and Isolation Of Antibiotic-resistant mentioning
confidence: 99%